1989
DOI: 10.1007/978-3-662-08539-4
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical Biology

Abstract: Cover pieture: A model based on a system of reaction-diffusion equations has been suggested by the author ofthis book to explain how the coat markings on the leopard and other mamma!s are generated. In this book, he gives a whole range of anima! patterning examples -from the stripes on the zebra to the eyespots on the wings ofbutterflies -to demonstrate the wide applicability ofsuch models.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
756
1
24

Year Published

1998
1998
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 2,383 publications
(785 citation statements)
references
References 0 publications
4
756
1
24
Order By: Relevance
“…Whether these other models exhibit qualitatively similar behaviour in response to growth is the subject of current investigation. Murray (1993) and Goodwin et al (1993) have discussed other scenarios in which the pattern selection problem may be overcome. If patterning is initiated from one sub-region of a domain, then a global pattern may form behind a moving front, generally increasing reliability for the selection of the pattern wavelength.…”
Section: 2mentioning
confidence: 99%
“…Whether these other models exhibit qualitatively similar behaviour in response to growth is the subject of current investigation. Murray (1993) and Goodwin et al (1993) have discussed other scenarios in which the pattern selection problem may be overcome. If patterning is initiated from one sub-region of a domain, then a global pattern may form behind a moving front, generally increasing reliability for the selection of the pattern wavelength.…”
Section: 2mentioning
confidence: 99%
“…For example, Meinhardt (1982) showed that diverse stripe and spot patterns, observed in developmental pattern formation, could be generated by a simple system of chemical interaction between two factors. Moreover, Murray (1989) explained various phenomena of biological pattern formation, including pattern formation in animal pigmentation. Many animal species have characteristic coat patterns on the skin.…”
Section: Introductionmentioning
confidence: 99%
“…There are three main types of interspecific interaction: predator-prey, competition, and mutualism. In a predator-prey relationship, the predator species benefits from killing and consuming the prey species, and the prey population size may be regulated as a result (Murray, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Traveling wave fronts are solutions to partial differential equations (PDEs), which have a fixed shape and translate at a constant speed c as time evolves. (See Murray, 1989 for a detailed discussion. )…”
Section: Introductionmentioning
confidence: 99%